Secondhand smoke exposure and survival following acute coronary syndrome: prospective cohort study of 1261 consecutive admissions among never-smokers. Issue 17 (14th August 2009) - Pell, J P; Haw, S; Cobbe, S; Newby, D E; Pell, A C H; Fischbacher, C; Pringle, S; Murdoch, D; Dunn, F; Oldroyd, K; MacIntyre, P; O'Rourke, B; et al.
Abstract : Objective: To determine whether exposure to secondhand smoke is associated with early prognosis following acute coronary syndrome. Design, setting and participants: We interviewed consecutive patients admitted to nine Scottish hospitals over 23 months. Information was obtained, via questionnaire, on age, sex, smoking status, postcode of residence and admission serum cotinine concentration was measured. Follow-up data were obtained from routine hospital admission and death databases. Results: Of the 5815 participants, 1261 were never-smokers. Within 30 days, 50 (4%) had died and 35 (3%) had a non-fatal myocardial infarction. All-cause deaths increased from 10 (2.1%) in those with cotinine ⩽0.1 ng/ml to 22 (7.5%) in those with cotinine >0.9 ng/ml (χ 2 test for trend p<0.001). This persisted after adjustment for potential confounders (cotinine >0.9 ng/ml: adjusted OR 4.80, 95% CI 1.95 to 11.83, p = 0.003). The same dose response was observed for cardiovascular deaths and death or myocardial infarction. Conclusions: Secondhand smoke exposure is associated with worse early prognosis following acute coronary syndrome. Non-smokers need to be protected from the harmful effects of secondhand smoke.